Applied Ecology in Forestry - Seth, S. K. (Indian Forester, 1955)
In the field of forestry, ecology has its principal application in the techniques of Silviculture. The first desideratum is a practical classification of forest areas into primary forest types. It is in this perspective that the following four aspects should be considered, which have been chosen to illustrate the main patterns of ecological approach involved in practical silviculture: ( i ) Silvicultural systems with natural regeneration. ( ii ) Silvicultural systems with artificial regeneration. ( iii) Subsidiary silvicultural operations. ( iv) Introduction of exotics. Under the first category are included the standard techniques of natural regeneration, based on the syn-ecology of the dominant communities. These are examples of applied syn-ecology within the framework of a system of management. The second section lays .tress on the application of aut-ecological knowledge in the formation of plantations, or the creation and establishment of "abnormal" tree communities. The third section embodies somewhat localized cultural practices which illustrate the synthesis of syn- and aut-ecological principles as applied to subsidiary and subdominant communities (including regeneration of the dominant tree species) under the main canopies of a tree forest. The last category deal. With an aspect of forestry in which the correct valuation of complex syn- and aut-ecological factors should precede experimentation and where eventual success may depend upon the nicety with which such factors are assessed. A few examples are cited.